Uso de bandejas de alimentação na fase de engorda do camarão-da-Amazônia Macrobrachium amazonicum (HELLER, 1862) - Preto, Bruno de Lima [UNESP]; Pizzato, Gustavo Maciel [UNESP]; Valenti, Wagner Cotroni [UNESP] (Inst Pesca, 2008)
The aim of this experiment was to evaluate the hypothesis that the M. amazonicum prawns accept feeding in trays. Six ponds were stocked with 10 juveniles II (1.2 +/- 0.7 g) per m(2) in 02/14/2003. An entirely randomized experimental design with 2 treatments (feeding in trays or feeding to the throw) and 3 replicates was used. Prawn average weight, survival, productivity, and physical and chemical variables of the water were compared between treatments using "t" test of Student. Average weight, survival and productivity were, respectively, 7.2 +/- 0.3 g, 46.8 +/- 7.8% and 335 +/- 45 kg/ha in feeding tray treatment and 6.8 +/- 0.1 g, 85.8 +/- 5.2% and 586 +/- 42 kg/ha in feed to the throw treatment. Survival and productivity differed significantly (p<0.5), while that average weight didn't differ significantly. M. amazonicum needs to use further number of trays per area, possibly due to territorial and aggressive behavior.
Use of feeding trays on grow-out phase of amazon river prawn, Macrobrachium amazonicum (HELLER, 1862)
Keywords: Macrobrachium amazonicum; grow-out phase; feeding in trays